Aquatic fungal diversity assessment through metagenomics is still limited to current databases - Anushree Sanyal; Mariana Kluge; Miguel Angel Redondo; Moritz Buck; Maliheh Mehrshad; Sarahi L. Garcia; Stefan Bertilsson; Sari Peura (Limnology and Oceanography, 2025)
Fungi play essential roles across ecosystems, yet their diversity in aquatic environments remains poorly understood compared to terrestrial systems. To address this gap, we analyzed metagenomes from 26 lakes in the boreal and subarctic zones, along with one tropical reservoir, to characterize fungal and fungal‐like (Oomycota) community structure. We also examined environmental factors shaping these communities. Most variation in fungal composition was explained by lake identity, depth layer, and season, with total organic carbon as a significant explanatory variable. Despite geographic and time differences, dominant fungal phyla, orders, and genera were largely consistent across all lakes. However, genus‐level variation indicated distinct community compositions likely influenced by differences in carbon substrate availability. Attempts to classify metagenomic reads down to the species level—illustrated here through the well‐characterized oomycete genus Phytophthora —were constrained by the limited taxonomic resolution of current reference databases. While metagenomics offers powerful means to investigate entire microbial communities, our results underscore a persistent bottleneck: the insufficient representation of aquatic eukaryotic genomes in public databases.